Extrastriatal degeneration correlates with deficits in the motor domain subscales of the UHDRS - Gálvez , Víctor; Ramírez-García, Gabriel; Hernandez-Castillo, Carlos R.; Bayliss, Leo; Díaz, Rosalinda; Lopez-Titla, María Margarita; Campos-Romo, Aurelio; Fernandez-Ruiz, Juan (My University, 2018)
Introduction: Striatal degeneration has significant behavioral effects in patients with Huntington's disease (HD). However, there is scant evidence of the possible contribution of extrastriatal regions to the motor alterations assessed within the different domains of the Unified Huntington's Disease Rating Scale (UHDRS). Objective: Analyze if extrastriatal grey matter decrease in patients with HD correlates with motor performance assessed with the UHDRS and its different domains. Method: Twenty-two molecular diagnosed patients with incipient HD, and twenty-two control participants matched for sex and age participated in this study. Voxel-based morphometry (VBM) analyses were done to identify grey matter decrease in the HD patients, and its relationship with the motor deterioration measured with the UHDRS motor scale. To further explore this relationship, a principal component analysis (PCA) was done on the UHDRS domains scores. Then the average of each component was used as a covariate in a VBM analysis. Finally, individual sub-scores from each domain were also tested for correlations with the VBM results.